REVIEW: ANALYSIS OF FERTILIZER USE ON PALM HARVEST RESULTS - Irham, Wardatul Husna; Friska Anggraini Barus; Marzuti Isra; Sri Wahyuna Saragih; Andrew Ivanovic Purba (Agro Estate, 2024)
Literature research has been carried out on the use of fertilizer on oil palm plants with several types of fertilizer. The aim of this research is to see the effect of several types of fertilizer on palm oil yields. The method used in this research is a literature review. Research results show that the fertilizers often used are chicken manure, goat manure, compost and cow urine. Providing animal manure fertilizer at doses of 0, 50, and 100 g/polybag had the same effect on the development of the upper seedlings, while a dose of 50 g/polybag had the best effect on the development of the lower seedlings. Fertilizer greatly influences the level of soil fertility, thereby increasing the number of leaves, the health of palm stems and palm harvest yields.